Rede social: desvendando a teia de relações interpessoais da nutriz - Marques, Emanuele Souza; Cotta, Rosângela Minardi Mitre; Botelho, Maria Izabel Vieira [UNESP]; Franceschini, Sylvia Do Carmo Castro; Araújo, Raquel Maria Amaral; Lopes, Lílian Lelis (IMS-UERJ, 2010)
This is a qualitative study resulting from matters involving the nursing mother social system regards to relation between social system and breastfeeding phenomena. The study was based on the social system theory described by Sanicola as well as on the social representations theory described by Moscovici and Minayo. As participants of this study there were mothers, fathers and grandparents of children up to two years old who were living in Coimbra, a city of Minas Gerais state. A comprehensive analysis of nursing mother social system revealed it can or can not give support to breastfeeding success. Thus the support was expressed by different ways such as: 1- housework helping; 2- babysitting; 3- breastfeeding encouragement; 4- orientation and advices. In this way a social system implies realizing which sociocultural context a woman-mother is inserted in. It enlarges the looking over breastfeeding besides giving subsidies to formulate public politics more efficacious in favour of breastfeeding.

Este é um estudo qualitativo que se refere à relação da rede social e a amamentação. Como fundamentação teórica, utilizou-se a Teoria da Rede Social de Sanicola, bem como a Teoria das Representações Sociais descrita por Moscovici e Minayo. Participaram do estudo mães, pais e avós, de crianças até dois anos, residentes no município de Coimbra-MG. A análise compreensiva da rede social da nutriz revelou que esta pode oferecer apoio/suporte ou não para o sucesso da lactação. Assim sendo, o apoio recebido foi expresso de várias formas: (1) Auxílio nas atividades domésticas; (2) Ajuda nos cuidados com o bebê; (3) Estímulo ao aleitamento; e (4) Orientações e conselhos. Nessa perspectiva, pensar em rede social implica conhecer o contexto sociocultural no qual a mulher-mãe está inserida, ampliando o olhar sobre a lactação, além de fornecer subsídios para a formulação de políticas públicas mais eficazes em prol do aleitamento.
Social network: revealing the nursing mother social affairs
Keywords: breastfeeding; family; health professional and social network; aleitamento materno; família; profissional de saúde e rede social